PENERAPAN TERMS FREQUENCY-INVERSE DOCUMENT FREQUENCY PADA SISTEM PERINGKASAN TEKS OTOMATIS DOKUMEN TUNGGAL BERBAHASA INDONESIA - Mulyana, Iyan; Ramadona, Sena; Herfina, Herfina (Proceedings of KNASTIK, 2012)
Automated Text Summarization is a process that utilize an computer application toproduce summary from a document and have the same meaning form document. Theresearch purposed is to develop an application that produce single document summaryin Bahasa Indonesia dynamically. This application quote the majority core meaning ofdocument and display to user the summary. Implementing of Term Frequency-InverseDocument Frequency (TF-IDF) count weight and relation between text. Input andoutput document form a document in Bahasa Indonesia. Input document consist of title,heading and text while the output document is essense of the document. Thisexperimental result shows that accuracy is 61%.